2014
DOI: 10.1103/physrevlett.112.068104
|View full text |Cite
|
Sign up to set email alerts
|

DNA Flexibility on Short Length Scales Probed by Atomic Force Microscopy

Abstract: Unusually high bending flexibility has been recently reported for DNA on short length scales. We use atomic force microscopy (AFM) in solution to obtain a direct estimate of DNA bending statistics for scales down to one helical turn. It appears that DNA behaves as a Gaussian chain and is well described by the worm-like chain model at length scales beyond 3 helical turns (10.5nm). Below this threshold, the AFM data exhibit growing noise because of experimental limitations. This noise may hide small deviations f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 41 publications
5
62
2
Order By: Relevance
“…shows substantially more flexibility than expected [31][32][33][34][35], although this observation of increased flexibility seems to be somewhat controversial [36][37][38].…”
Section: Biological Relevance Of Different Length Scalesmentioning
confidence: 69%
See 1 more Smart Citation
“…shows substantially more flexibility than expected [31][32][33][34][35], although this observation of increased flexibility seems to be somewhat controversial [36][37][38].…”
Section: Biological Relevance Of Different Length Scalesmentioning
confidence: 69%
“…Because these mechanical probes require long dsDNA -albeit recently short DNA segments within long dsDNA was also probed using high-resolution AFM [31,34,37,38]; however some work suggest that the properties of short dsDNA are contrary to those of a short segment in a long dsDNA [87] -the short finite-length (e.g. < 50 base-pairs; < 20 nm) polymeric behavior of free dsDNA is not as well understood.…”
Section: Double-stranded Dna Polymer Propertiesmentioning
confidence: 99%
“…Similarly, another j-factor measurement of ∼116 bp DNA by Forties et al [34] also reported a canonical WLC elastic response of looped DNA, except when multiple weak ATA repeats were introduced into the sequence and when the experiments were carried out at higher temperatures (>30°C). In addition, a more recent in-fluid AFM imaging measurement of ( ) with refined imaging analyses reported a canonical WLC elastic response of DNA at large bending angles [28]. Consistently, a recent cryo-EM imaging of 94 bp DNA loops did not observe mechanical bending defects inside the DNA molecules [35].…”
Section: Debate On the Anomalous Mechanics Of Sharply Bent Dnamentioning
confidence: 80%
“…For example, single-molecule stretching experiments are not suitable because of the additional suppression of sharp DNA bending by tensile forces. Furthermore, although AFM imaging measurements of ( ) have been used to probe the probability of large bending angles over short contour separations [10], there is concern regarding whether some of the observed rare sharp bends are artifacts due to DNA surface interactions and complex imaging analysis processes [28].…”
Section: Anomalous Mechanics Of Sharply Bent Dnamentioning
confidence: 99%
“…[45] and with general studies of mesoscopic models fitting mechanical opening experiments on single molecules [46]. The elastic force constant K S is taken in the low range of the reported values [47,48] as it seems appropriate to capture the intrinsic flexibility displayed by the helix at the microscopic level [49,50].…”
Section: Partition Functionmentioning
confidence: 99%